Pengaruh Ulasan Produk Dan Harga Terhadap Keputusan Pembelian Bouquet Pada Shopee Bylinar Di Daerah Khusus Jakarta - Linarotul Fitriah; Irmal Irmal (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of product reviews and price on purchasing decisions for bouquet products on Shopee ByLinar using a descriptive quantitative method. The research sample consisted of 97 respondents selected through probability sampling using the Slovin formula, and the data were analyzed using SPSS version 29. The results show that product reviews have a positive and significant effect on purchasing decisions with the regression equation Y = 7.971 + 0.819X₁, a correlation coefficient of 0.735, and a coefficient of determination of 56.3%, while price also has a positive and significant effect with the regression equation Y = 5.047 + 0.897X₂, a correlation coefficient of 0.886, and a coefficient of determination of 78.3%. Simultaneously, product reviews and price have a positive and significant effect on purchasing decisions with the regression equation Y = 1.697 + 0.220X₁ + 0.753X₂, a correlation coefficient of 0.896, and a coefficient of determination of 80.3%, supported by t-test values of 11.232 and 18.915 and an F-test significance value of < 0.05. Therefore, it can be concluded that product reviews and price are important factors influencing purchasing decisions for bouquet products on Shopee ByLinar.